Preoperative malignant looking retrobulbar, infratemporal and middle cranial fossa tuberculoma in a young child - a case report (Bangladesh Journal of Medical Science, 2014)
Tuberculosis involving skull base and brain is relatively common in developing countries. Preoperative neuro-radiological features of such lesions mimic neoplastic lesions of brain & skull base and postoperative histopathological study brings the ultimate diagnosis. Here we present a case of large tubercular lesion involving retrobulbar, infratemporal and middle cranial fossa that preoperatively thought to be a malignant lesion in a young child and was managed surgically with anti-tubercular drugs having a happy termination. Even radiologically malignant looking mass lesion in brain and skull base can be proved as tuberculosis that can bring happiness to the patient and also to the treating neurosurgeons. DOI: http://dx.doi.org/10.3329/bjms.v13i3.7518 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.323-325